2014
DOI: 10.3906/bot-1310-14
|View full text |Cite
|
Sign up to set email alerts
|

Census, reproductive biology, and germination of Astragalus gines-lopezii (Fabaceae), a narrow and endangered endemic species of SW Spain

Abstract: Abstract:Astragalus gines-lopezii Talavera, Podlech, Devesa & F.M.Vazquez (Fabaceae) is a threatened endemic species with a distribution restricted to a very small area in Badajoz Province (Extremadura Region, SW Spain) and only 2 populations are known. This species was catalogued in the "Endangered" category in the 2008 Red List and the 2010 Threatened Spanish Vascular Flora List. Despite its status as an endangered species, at present very little is known about the distribution, census, and reproductive biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
4
13
0
2
Order By: Relevance
“…The experiments showed a positive effect of mechanical scarification on seed germination, because this method increased the percentage of germinating seeds to 100%. It is in totally agreement with results obtained for A. gines-lopezii [7] and A. siliquosus [13] for which scarification with sandpaper significantly enhanced seed germination. Physical scarification turned out to be the best method of breaking dormancy also for A. arpilobus [14] and A. cicer [12].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The experiments showed a positive effect of mechanical scarification on seed germination, because this method increased the percentage of germinating seeds to 100%. It is in totally agreement with results obtained for A. gines-lopezii [7] and A. siliquosus [13] for which scarification with sandpaper significantly enhanced seed germination. Physical scarification turned out to be the best method of breaking dormancy also for A. arpilobus [14] and A. cicer [12].…”
Section: Discussionsupporting
confidence: 91%
“…There are several methods for breaking physical dormancy revised by Rolston [5]. Dormancy and germination of seeds from the genus Astragalus has been studied in some rare and endangered species, e.g., A. adsurgens [6], A. gines-lopezii [7], A. nitidiflorus [8], A. maritimus, and A. verrucosus [9] due to the fact that it is crucial for their reproduction, ex situ conservation and reintroduction.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the seeds were stored for 1 year before they were tested for germination it is not known if fresh seeds were dormant or non-dormant. The results of Ramos et al (2010) do not agree with those of Martínez-Fernández et al (2014), who compared dormancy/germination of the only two known populations of A. gines-lopezii . They found that mechanical scarification increased mean germination from 27 to 95% in the Andres population and from 30 to 91% in the Calera population.…”
Section: Resultsmentioning
confidence: 79%
“…Great intra-population variability in germination has been detected in several wild Mediterranean species, such as Erica australis (Cruz et al ., 2003), Ceratonia siliqua (Pérez-García, 2009), Astragalus gines-lopezii (Martínez-Fernández et al ., 2014), Senecio coiincyi (Martínez-García et al ., 2012), Gentiana lutea (Pérez-García et al ., 2012), and several species of Cistaceae (Pérez-García, 1997; Tavşanoğlu and Çatav, 2012). In the Mediterranean climate, with variable and unpredictable environmental conditions, an important survival strategy of wild species would be variation in either germination requirements (Kigel, 1995; Cruz et al ., 2003; Pérez-García et al ., 2003; Pérez-García, 2005; Pérez-García et al ., 2006; Pérez-García and González-Benito, 2012; Pérez-García et al ., 2012; Baskin and Baskin, 2014; Copete et al ., 2014; Martínez-Fernández et al ., 2014), seed dormancy (Pérez-García et al ., 2012), seed longevity (Mira et al ., 2011a; Lazar et al ., 2014; Mira et al ., 2015a) or seed characteristics (Pérez-García et al ., 2006; Mira et al ., 2011b; Pérez-García and González-Benito, 2012). In nature, P. angustifolia flowering takes place in March to June, fruits ripen in September to October and are dispersed from September to March.…”
Section: Discussionmentioning
confidence: 99%